RETRACTED: The Influence of Service Quality, Sales Promotion, and Brand Trust on Customer Satisfaction of Baraya Travel Kebayoran Baru, South Jakarta in 2019 - Aji Prasetya Pangestu; Elwisam Elwisam; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to analyze the effect of Service quality, sale promotion, and brand trust on customer satisfaction at baraya travel Kebayoran baru South Jakarta 2019. The data of this Study used primary data in the form of questionnaires do 100 employees of baraya travel Jakarta. Data analysis techniques using multiple linear regression analysis Ana using The program SPSS program. The results showed an influence between Service quality, customer satisfaction of 0,280 and an influence of 28,0 % similary, the variable sale promotion on Customer satisfaction of 0,316 and has an influence of 31,6 %. then for the variable Brand satisfaction on Customer satisfaction of 0,303 and has an influence 30,3 %. Partially or simultaneously have a strong influence among the Three variables, the most significant is Band Trust variable of 0,000. The result and of this study expect do improve Service quality that can support Customer satisfaction.